Decoding an Old 1907 Prescription of Dr. Ing Hay ("Doc Hay"): One of the Earliest Chinese Medicine Doctors in the United States - Arthur Yin Fan; Louis Lei Jin; Boling Huang; Mingxia Yu; Xiaoyin Zhao; Sarah Faggert Alemi (Wolters Kluwer Health/LWW, 2020)
Objectives:. Chinese medicine doctors have practiced in the United States since April of 1854, the world's first Chinese medicine doctor's memorial is Kam Wah Chung Museum in John Day, Oregon, U.S., to commemorate Dr. Ing Hay ("Doc Hay" 伍于念) and his business partner Lung On (梁光荣). There were few studies to explore Doc Hay's real practice and prescription, while most of papers focused on Doc Hay's legend life. This paper aims to analyze and interpret one of the intriguing herbal prescriptions that Doc Hay had hand-written. Materials and Methods:. Dr. Arthur Yin Fan made an academic travel to Kam Wah Chung museum on August 5, 2018 and examined the books and hand-written prescriptions of Doc Hay, which were not exhibited to the public at that time. This paper analyzes and interprets one of herbal prescriptions that Doc Hay had hand-written in 1907. Interpretation process included four steps: (1): Transform Doc Hay's hand-written prescription (with original herb names) to standard herb names in Chinese. (2): Induct and rearrange the herb name into groups based on herb property characteristics and then translate them into both PinYin names and English names. Analyzation of the prescription may include in what classic formula (s) routinely introduced in Chinese medicine textbooks. (3): Analyze the herbal action for each group and potential symptoms or conditions the patient may have had. An analysis of classic formula (s) used in the prescription may represent what clinical condition was being treated at that time. (4): Combine the analysis to give a comprehensive picture of the patient. Results:. The prescription consists of 67 herbs, total 934.6 grams, and including Yin Qiao Powder (银翘散), Sang Ju Decoction (桑菊饮), Zhi Sou Powder (止嗽散), Qing Ying Decoction (清营汤), Xi Jiao Di Huang Decoction (犀角地黄汤), Long Dan Xie Gan Decoction (龙胆泻肝汤) and Chai Hu Shu Gan Powder (柴胡疏肝散). Speculation indicated that the prescription was for a patient who had obvious pulmonary infection accompanied by severe cough, and probably had prolonged pulmonary tuberculosis (TB) also with acute respiratory infection caused by other bacteria or viruses. Based on the analysis of composition of this prescription, it can be used for the treatment of epidemic diseases. Conclusion:. The majority of herbs used in this prescription are commonly included in the herbal medicines in China used to effectively counter severe acute respiratory syndrome (SARS), H1N1 and currently COVID-19, it might be Doc Hay's basic formula for patients with "Spanish Flu" during the 1918-1920 pandemic.